Effects of adiponectin on the progression of breast cancer: role of Estrogen Receptor alpha - Ricchio, Emilia; Sisci, Diego; Mauro, Loredana (My University, 2014)
Adipose tissue is no longer considered an inert tissue for storing energy but is now recognized as an active endocrine organ secreting adipokines, cytokines and a diverse range of inflammatory markers. Adiponectin is one of the adipokines secreted by white adipose tissue and has been suggested to improve insulin sensitivity, regulate glucose and lipid metabolism and might play a role in the development of diabetes and atherosclerosis. In addition, it appears to play an important role also in the development and progression of several obesity-related malignancies, including breast cancer. In the present study, we demonstrated that adiponectin induces a dichotomic effect on breast cancer growth. Indeed, it stimulates growth in ERα-positive MCF- 7 cells while it inhibits proliferation of ERα-negative MDA-MB-231 cells. Notably, only in MCF-7 cells adiponectin exposure exerts a rapid activation of MAPK phosphorylation, which is markedly reduced when knockdown of the ERα gene occurred. In addition, adiponectin induces rapid IGF-IR phosphorylation in MCF-7 cells, and the use of ERα siRNA prevents this effect. Moreover, MAPK activation induced by adiponectin was reversed by IGF-IR siRNA. Coimmunoprecipitation studies show the existence of a multiprotein complex involving AdipoR1, APPL1, ERα, IGF-IR, and c-Src that is responsible for MAPK signaling activation in ERα-positive breast cancer cells. It is well known that in addition to the rapid effects through non-genomic mechanisms, ERα also mediates nuclear genomic actions. In this concern, we demonstrated that adiponectin is able to transactivate ERα in MCF-7 cells. We showed the classical features of ERα transactivation: nuclear localization, downregulation of mRNA and protein levels, and upregulation of estrogen dependent genes. Finally we demonstrate that in vivo adiponectin (1 and 5 μg/ml) induces a significant reduction (60 and 40%, respectively) in tumor volume in animals injected with human ERα-negative MDA-MB-231 cells, whereas an increased tumor growth (54 and 109%, respectively) is observed in the animals receiving human ERα-positive MCF-7 cells. Moreover, cyclin D1 (CD1) mRNA and protein levels are decreased in MDA-MB-231 cells, while they are upregulated in MCF-7 cells by adiponectin. Collectively, this study clarifies the molecular mechanism through which adiponectin modulates breast cancer cell growth, providing evidences on the celltype dependency of adiponectin action in relationship to ERα status.
Dottorato di Ricerca in Biochimica Cellulare ed Attività dei Farmaci in Oncologia, XXVII Ciclo, a.a. 2013-2014
Keywords: Biochimica cellulare; Adipociti; Citochine